2011
DOI: 10.3233/jad-2011-110405
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Sphingomyelins are Associated with Cognitive Progression in Alzheimer's Disease

Abstract: Plasma sphingolipids have been shown to predict cognitive impairment and hippocampal volume loss, but there is little research in patients with Alzheimer’s disease dementia (AD). In this study we sought to determine whether plasma ceramides, dihydroceramides (DHCer), sphingomyelins (SM), or dihydrosphingomyelin (DHSM) levels and ratios of SM/ceramide or DHSM/DHCer were predictive of progression in AD. Probable AD patients (n=120) were enrolled in the Alzheimer’s Disease and Memory Disorders Center at Baylor Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
108
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(131 citation statements)
references
References 40 publications
16
108
1
6
Order By: Relevance
“…10 These cause synaptic dysfunction and spine loss, and correlate most closely with the severity of human AD. 5,8,11 Recent biochemical studies indicated that natural sphingolipids and gangliosides, whose metabolism has been shown to be altered in AD patients, 12 destabilize and rapidly resolubilize long Ab fibrils to neurotoxic species. 13 These studies also showed that phospholipids stabilize toxic oligomers from monomeric peptides.…”
mentioning
confidence: 99%
“…10 These cause synaptic dysfunction and spine loss, and correlate most closely with the severity of human AD. 5,8,11 Recent biochemical studies indicated that natural sphingolipids and gangliosides, whose metabolism has been shown to be altered in AD patients, 12 destabilize and rapidly resolubilize long Ab fibrils to neurotoxic species. 13 These studies also showed that phospholipids stabilize toxic oligomers from monomeric peptides.…”
mentioning
confidence: 99%
“…Наиболее высокое содержание церамида было обнаружено при средней тяжести заболевания по сравнению с начальной и тяжелой [104].…”
Section: сфинголипиды в спинномозговой жидкости при баunclassified
“…Тем не менее, в литературе обсуждается возможность использования церамидов в качестве маркеров БА [104][105][106]. Некоторым ограничением может служить неспецифичность этого параметра для БА, поскольку уровень церамидов в СМЖ меняется и при других нейропатологиях.…”
Section: сфинголипиды в спинномозговой жидкости при баunclassified
See 2 more Smart Citations